2017
DOI: 10.1007/s40092-017-0241-7
|View full text |Cite
|
Sign up to set email alerts
|

A maintenance system model for optimal reconfigurable vibrating screen management

Abstract: The reconfigurable vibrating screen (RVS) machine is an innovative beneficiation machine designed for screening different mineral particles of varying sizes and volumes required by the customers' through the geometric transformation of its screen structure. The successful RVS machine upkeep requires its continuous, availability, reliability and maintainability. The RVS machine downtime, which could erupt from its breakdown and repair, must also be reduced to the barest minimum. This means, there is a need to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm this assertion, a combination of two very popular risk assessments tools (fault tree analysis and reliability block diagram) was used to investigate one of the most recent power transformer bushing failures. Fault tree (FTA) [15,53,54,[65][66][67][68][69][70][71] and reliability block diagrams (RBD) [53,54,[72][73][74][75] are very illustrative performance evaluation tools that have been immensely used for investigating critical plant failures across a variety of industries within the last five decades.…”
Section: Ae1: Maintenance Strategy and Planning Activitiesmentioning
confidence: 99%
“…Based on this premise and to foster practical knowledge transfer, a team-based FTA was employed at PLN. It is vital to note that besides visually representing the relationships between various causal factors of an FTA, it is also possible to estimate the probability of occurrence of the "unwanted" or "top event" using Equations (1) and (2) [53,54,[65][66][67][68][69][70][71]76];…”
Section: Ae1: Maintenance Strategy and Planning Activitiesmentioning
confidence: 99%